Fire response of the endangered Pinus culminicola stands after 18 years in Cerro El Potosí, northeast Mexico - Arévalo, José R.; Estrada, Eduardo; Encina, Juan A.; Villareal, José A.; Escobedo, Job R.; Morales, Yaretzi; Cantú, Israel; González-Rodríguez, Humberto; Uvalle, José (Forest Systems, 2017)
Aim of the study: To analyze the impact of the 1998 wildfire on dwarf pine (Pinus culminicola) population stands 18 years after the fire.Area of study: Cerro el Potosí, Nuevo León (México)Material and methods: We measured regeneration, biovolume of individuals, diversity and species composition in unburned and burned plots randomly selected in the area.Main results: Recovery was very slow, with limited dense natural regeneration and very slow growth. Significant differences between control and burned plots were found with respect to regeneration, species composition, evenness and soil nutrients, suggesting that fire could promote natural regeneration and biodiversity in these communities.Research highlights: Management efforts are necessary to maintain a natural fire regime and ensure grazing exclusion in order to favor the conservation of the community dominated by this rare species P. culminicola.